Students’ Paragraph Errors and Its Implication for Teaching Writing - Sahan, Anselmus (Soegijapranata Catholic University, 2022)
This paper aims to expose the students’ ability to write a simple passage. To get the data needed, the writer asked them to write a simple paragraph of Indonesian consisting of five sentences and translate it into English. To analyze their writings, he gave three codes on their writings (italic, bold, and underline words). Their errors on writing were classified on the basis of Dulay, Burt Krashen’s (1982) four types of surface strategy taxonomy consisting of omission, addition, misformation and misordering. The results reveal that the students made 33 omission, 32 addition, 9 misformation, and 8 misordering errors. So, they still have difficulties to write a paragraph. Therefore, teaching and learning process of writing subject should teach students to be able to write acceptable, efficient and effective paragraphs.